A Study on the Internet Addiction among College Students in Chennai - K.S. , Ramakrishnan (International Journal of Computer Sciences and Engineering, 2019)
The present study viz., A study on the Internet Addiction among college students in Chennai District is an attempt to find out the level of internet addiction and if there is any significant difference in Internet addiction of college students with respect to type of family and Annual income of the Family. Internet Addiction Test (IAT) standardized by Rajhuewar (2009) was used for the study and it was administered to 300 college students studying in four arts and science colleges by applying simple random sampling technique. Mean Standard Deviation and t -tests were calculated to test the hypotheses. The findings of this study revealed that the level of internet addiction of college students is high and there is there is significant difference in Internet addiction of college students with respect to type of family and annual income of the Family. The present paper highlights the major issues related to the Internet addiction among the youngsters. It is an alarm bell for the situation prevailing and gradually increasing trend in India.